PENGARUH BEBAN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA ASN DENGAN LINGKUNGAN KERJA SEBAGAI VARIABEL MODERATING PADA DINAS KESEHATAN SITUBONDO - Rizal, Ardi Usmaul; Tulhusnah, Lusiana; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Human resources are an important aspect that determines the success of a company in achieving its goals and objectives. Proper employee job placement is one of the key elements in human resource management to support this achievement. The aim of this research is to analyze the effect of the variables of Workload and Leadership Style on the Performance of Civil Servants (ASN) with Environment as a moderating variable at the Situbondo Health Office. The population in this study involves 40 ASN of the Situbondo Health Office excluding the leaders. Sampling in this research was conducted using the saturated sampling technique, which means that all members of the population were included as samples. The Partial Least Squares Structural Equation Model (PLS-SEM) was used for data analysis and hypothesis testing. The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that workload has a significant positive effect on performance, leadership style has a significant positive effect on performance, the work environment moderates the effect of workload on performance, and the work environment does not moderate the effect of leadership style on performance.